Demonstrating Transit Schedule Benefits with a Dedicated Short-Range Communication-Based Connected Vehicle System. Issue 12 (December 2019) - Leonard, Blaine D.; Mackey, Jamie; Sheffield, Michael; Bassett, David; Larson, Shawn; Hooper, Ivan
A vehicle-to-infrastructure (V2I) connected vehicle system was installed along Redwood Road in Salt Lake City, Utah, United States, in November 2017 using dedicated short-range communication (DSRC) radios to connect transit buses to traffic signals. One of the goals of this system was to improve the schedule reliability of the bus by providing signal priority at traffic signals when the bus is behind its published schedule by a certain threshold. Data for the analysis were obtained from the DSRC communications, the Automated Traffic Signal Performance Measures (ATSPM) system, and the transit operations system. The robust data available from these three systems allow for detailed analysis of priority requests made, requests served, and bus on-time performance in a way that is not possible without these data sets. By comparing actual schedules of the four DSRC-equipped buses over a 4-month period from April to July 2018 with buses which do not have the ability to request signal priority, it has been determined that the equipped buses meet their published schedule about 2% to 6% more frequently, depending on direction and time of day, with the most significant improvement of 6% in the southbound PM peak.